Hubungan Pola Makan dan Kadar Hb Pada Remaja Putri - Suwanti; Erna Widyastuti; Fina Nurul Azizah (Midwifery Care Journal, 2026)
The prevalence of anemia in adolescent females constitutes a notable public health issue, given its potential detrimental implications for growth, development, and academic achievement. Dietary patterns are commonly considered one of the contributing factors to anemia. This investigation sought to analyze the correlation between dietary patterns and hemoglobin (Hb) concentrations in adolescent females. A quantitative research methodology employing a cross-sectional design was implemented. The study population comprised 80 adolescent girls, of whom 76 were included as respondents using a total sampling technique. Dietary patterns were assessed using a structured questionnaire, while hemoglobin levels were measured using a hemoglobin testing device. The data were subjected to analysis employing both univariate and bivariate methodologies, with the Chi-square statistical test being utilized at a significance threshold of α = 0.05. The findings indicated that a higher proportion of adolescent girls with good dietary patterns had normal hemoglobin levels (81.8%) compared to those with adequate dietary patterns (66.7%). However, statistical analysis revealed a p-value of 0.148 (p > 0.05), suggesting that there was no statistically significant association between dietary patterns and hemoglobin levels among adolescent girls. In conclusion, hemoglobin levels in adolescent girls are influenced by multiple factors beyond dietary patterns alone. Therefore, comprehensive anemia prevention strategies, including nutrition education, regular health monitoring, and iron supplementation programs, are strongly recommended.